Improving Medication Error Reporting Through Clinical Audit and Targeted Interventions in a Tertiary Care Hospital - Chauhan, Shivani; Gaur, Ankit (Indian Journal of Pharmacy Practice)
Aim: Medication errors are a major threat to patient safety, with underreporting driven by fear, stigma, and lack of awareness. This study aimed to improve the culture of medication error reporting in a tertiary care hospital by implementing targeted interventions through clinical audit. Materials and Methods: A prospective observational audit was conducted across two 3-month cycles (March-May and June-August 2023). Errors were classified by NCC MERP guidelines and collected via clinical pharmacologist rounds and voluntary reports. A Medication Safety Committee analyzed Cycle 1 errors and implemented interventions, including staff training, chart reviews, and a comprehensive reporting form before Cycle 2. Results: Reported errors increased from 17 in Cycle 1 to 56 in Cycle 2, indicating improved staff engagement. Transcription errors dropped post-intervention, while administration, documentation, and prescribing errors rose, reflecting broader awareness. Statistical analysis revealed a significant difference in error type distribution (χ² = 11.95, p = 0.036). Conclusion: Interventions fostered a positive shift toward open reporting and enhanced patient safety. Sustaining this improvement requires longer audit durations, broader interdisciplinary involvement, and digital tools to minimize the burden of reporting.
Keywords: Medication Errors; Patient Safety; Clinical Audit; Medication Safety; Error reporting